The Twilight of Corporate Strategy: A Comparative Ethical CritiqueThe Twilight of Corporate Strategy: A Comparative Ethical Critique, by Gilbert Daniel R. Jr., New York: Oxford University Press, October, 1992, $29.95, cloth. - Post, James E. (Academy of Management Review, 1993)
The article reviews the book ?The Twilight of Corporate Strategy: A Comparative Ethical Critique,? by Daniel R. Gilbert Jr.